Does the mode of delivery affect mathematics examination results? - D. J. Fiddes; A. A. Korabinski; G. R. McGuire; M. A. Youngson; D. McMillan (Association for Learning Technology, 2002)
At present most examinations are delivered on paper but there is a growing trend in many subjects to deliver some or part of these examinations by computer. It is therefore important to know whether there are any differences in the results obtained by candidates sitting examinations taken by computer compared with those obtained by candidates sitting conventional examinations using pen and paper. The purpose of this article is to describe the outcome of a pilot study designed to* investigate possible causes of any differences in results from the use of different modes of delivery in a mathematics examination. One outcome of this study was that the process of translating examination questions into a format required for use on the computer (but keeping this as a pen and paper test) can have a significant effect on examination results. However, the main conclusion is that changing the medium only has no effect on the results in mathematics examinations.